A Conductive Metal−Organic Framework Based on Triptycene Ligand: An Effective Electrochemical Sensor for Glucose and H2O2 Detection in Food and Human Serum. Issue 3 (17th March 2023) - Hu, Qin; Wu, Jiaying; Ling, Chengshuang; Xing, Yun; Tang, Xin; Zhang, Yu; Huang, Ke; Ye, Jun; Xiong, Xiaoli
Abstract : Triptycenes (TT) scaffolds have emerged as attractive organic ligands for the synthesis of MOF electrocatalytic materials because their characteristic rigid trigonal topology interferes with close molecular packing, thus favoring the formation of open structures with significant volume available for the inclusion of guests. In this work, a novel conductive metal-organic framework based on 2, 3, 6, 7, 14, 15-hexahydroxytriptycene (Cu-HHTT) is synthesized in situ by a simple hydrothermal method. As an bifunctional electrocatalyst for efficient glucose electrooxidation and H2 O2 electroreduction in alkaline and neutral electrolytes, the non-enzymatic electrochemical sensor has a sensitivity of 47200 mA μ M −1 cm −2 and 5170 mA μ M −1 cm −2 to glucose and H2 O2 with detection limits of 0.16 μ M and 0.54 μ M (S/N = 3) respectively, and successfully used in the detection of actual serum, orange juice and milk samples. The method provides a new idea for the preparation and application of MOF materials based on triptycene scaffolds.